Analisis Yuridis terhadap Penggunaan Deepfake dalam Pelanggaran UU ITE: Studi Kasus di Media Sosial Indonesia (International Forum of Researchers and Lecturers, 2025)
The advancement of information and communication technology in the era of the Industrial Revolution 4.0 has given rise to various digital innovations, one of which is deepfake technology that utilizes artificial intelligence and machine learning to manipulate audio-visual content convincingly. Although it has positive potentials in entertainment and education, the misuse of deepfake on social media has caused various legal and ethical issues, such as the spread of hoaxes, defamation, privacy violations, and non-consensual pornography. This study aims to analyze the use of deepfake from the perspective of Indonesian law, particularly through Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law) and its amendments. Using a qualitative descriptive approach and literature study methods, this research examines the technical aspects of deepfake development, the relevance of ITE Law articles in regulating manipulative content, and the challenges of law enforcement amid low digital literacy in society. The findings show that although there are no explicit provisions concerning deepfake in the ITE Law, several articles can serve as a legal basis to prosecute offenders, albeit with interpretative and technical implementation challenges. Therefore, regulatory updates and improvements in digital literacy are necessary to prevent and effectively handle the misuse of deepfake technology.